Auto positive airway pressure therapy reduces pulmonary pressures in adults admitted for acute heart failure with pulmonary hypertension and obstructive sleep apnea. The ASAP-HF Pilot Trial. Issue 7 (20th April 2019) - Sharma, Sunil; Fox, Henrik; Aguilar, Francisco; Mukhtar, Umer; Willes, Leslee; Bozorgnia, Benham; Bitter, Thomas; Oldenburg, Olaf
Abstract: Objectives: Pulmonary hypertension (PH) is extremely common in acute decompensated heart failure (ADHF) patients and predicts increased mortality. Obstructive sleep apnea (OSA), highly prevalent in congestive heart failure patients, may contribute to further elevated pulmonary pressures. This study evaluates the impact of positive airway pressure (PAP) therapy on PH in patients admitted for ADHF with OSA. Methods: A two-center randomized control trial comparing standard of care (SOC) therapy for ADHF versus addition of PAP therapy in patients with concomitant OSA. Results: Twenty-one consecutive patients were enrolled with 1:1 randomization to SOC versus SOC plus 48-hour PAP therapy protocol. In the intervention arm, the mean pulmonary artery systolic pressure (PASP) difference before therapy and after 48 hours of PAP therapy was −15.8 ± 3.2 (58.6 ± 2.5 mm Hg to 42.8 ± 2.7) versus the SOC arm where the mean PASP difference was −5.2 ± 2.6 (62.7 ± 3.3 mm Hg reduced to 57.5 ± 3.9) ( p = 0.025). In addition, ejection fraction in the intervention arm improved (3.4 ± 1.5% versus −0.5 ± 0.5 %) ( p = 0.01). Significant improvement was also noted in tricuspid annular plane systolic excursion (TAPSE) and right ventricular systolic area in the intervention arm but not in NT-pro-BNP or 6-minute walk distance. Conclusions: In patients with ADHF and OSA, addition of 48 hours of PAP therapy to SOC treatment significantly reduced PH. In addition, PAP therapy was able to improve right and left ventricular function. ClinicalTrials.gov identifier: NCT02963597.